Harnessing Digital and Artificial Intelligence for Sustainable Development in Mauritius (African Journal of Public Administration & Management, 2026)
Digital technologies and AI are transforming governance (digital tools improving efficiency, transparency and citizen engagement), education (AI and VLC revolutionising learning), finance (epayment / fin-tech) & healthcare (telemedicine, AI).For SIDS like Mauritius, digital transformation offers great opportunities (diversification, Digital investment, global trade access & innovation) but also risks of digital exclusion (underserved communities) and technological dependency (concerns like cyber threats, data sovereignty)Anchored in the Mauritius Digital Transformation Blueprint 2025–2029 (DI, Innovation, AI, skills, cybersecurity), aligned with Vision 2030, Africa’s Digital Transformation Strategy, and the UN SDGs.
Keywords: ARTIFICIAL INTELLIGENCE; SUSTAINABLE DEVELOPMENT